2009
DOI: 10.1016/j.neuron.2009.12.019
|View full text |Cite
|
Sign up to set email alerts
|

LRRTM2 Interacts with Neurexin1 and Regulates Excitatory Synapse Formation

Abstract: Summary We identify the leucine-rich repeat transmembrane protein LRRTM2 as a key regulator of excitatory synapse development and function. LRRTM2 localizes to excitatory synapses in transfected hippocampal neurons, and shRNA-mediated knockdown of LRRTM2 leads to a decrease in excitatory synapses without affecting inhibitory synapses. LRRTM2 interacts with PSD-95 and regulates surface expression of AMPA receptors, and lentivirus-mediated knockdown of LRRTM2 in vivo decreases the strength of evoked excitatory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
389
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 334 publications
(412 citation statements)
references
References 35 publications
16
389
0
Order By: Relevance
“…All four LRRTM family members display synaptogenic activities in these assays, although the induction strength of LRRTM2 is the strongest (de Wit et al, 2009;Ko et al, 2009;Linhoff et al, 2009). LRRTM2 specifically localizes in excitatory synapses, and not in inhibitory synapses (Linhoff et al, 2009).…”
Section: Lrr Synaptic Adhesion Moleculesmentioning
confidence: 92%
See 4 more Smart Citations
“…All four LRRTM family members display synaptogenic activities in these assays, although the induction strength of LRRTM2 is the strongest (de Wit et al, 2009;Ko et al, 2009;Linhoff et al, 2009). LRRTM2 specifically localizes in excitatory synapses, and not in inhibitory synapses (Linhoff et al, 2009).…”
Section: Lrr Synaptic Adhesion Moleculesmentioning
confidence: 92%
“…A systematic bioinformatics study has shown that extracellular LRR domain-containing proteins have greatly expanded in mammals (135 in mouse, 139 in human) compared with worms (29 extracellular LRR proteins) and flies (66 extracellular LRR proteins) (Dolan et al, 2007). The ligands of these extracellular LRR proteins remain largely unknown, although the process of ligand identification has recently accelerated (de Wit et al, 2009;Ko et al, 2009;Siddiqui et al, 2010;Takahashi et al, 2011;Woo et al, 2009). Mounting evidence from invertebrate systems shows that extracellular LRR proteins control key phases of neuron development and neural circuit formation including axon guidance, target-cell recognition, and synapse formation.…”
Section: Leucine-rich Repeats (Lrrs)mentioning
confidence: 99%
See 3 more Smart Citations